Redigeringssystemet RiSt - udviklet og anvendt i et færøsk ordbogsmiljø - Zachariassen, Pertur; Hansen, Zakaris (Nordiske Studier i Leksikografi, 1995)
The objective of this paper is to present a computer program for dictionary editing. RiSt, as the program is called, is used in some dictionary projects in the Faroe Islands. The program enables the lexicographer to write and edit dictionary entries in a structural manner applying elements from a predefined set of categories and use familiar editing tools known from text processing programs. The entry elements are shown in categorydependent type styles, and RiSt automatically inserts punctuation marks between the entry elements. Optional input control can be placed on selected categories according to tables with preset or ongoing defined values. The user can pick out a selection of dictionary entries for printing and export (in a tag-format) according to search conditions including for instance word occurrence and username. RiSt supports PostScript-printers, and the user can ad just some lay-out paramaters toget various printing setups. The RiSt system has been developed as a joint project involving institutes at Fróðskaparsetur Føroya (University of the Faroe Islands) and the company Z-teld.